SPIDERS: an overview of the largest catalogue of spectroscopically confirmed x-ray galaxy clusters. Issue 4 (14th April 2021) - Kirkpatrick, C C; Clerc, N; Finoguenov, A; Damsted, S; Ider Chitham, J; Kukkola, A E; Gueguen, A; Furnell, K; Rykoff, E; Comparat, J; Saro, A; Capasso, R; et al.
ABSTRACT: SPIDERS is the spectroscopic follow-up effort of the Sloan Digital Sky Survey IV (SDSS-IV) project for the identification of X-ray selected galaxy clusters. We present our catalogue of 2740 visually inspected galaxy clusters as part of the SDSS Data Release 16 (DR16). Here we detail the target selection, our methods for validation of the candidate clusters, performance of the survey, the construction of the final sample, and a full description of what is found in the catalogue. Of the sample, the median number of members per cluster is approximately 10, with 818 having 15 or greater. We find that we are capable of validating over 99 per cent of clusters when five redshifts are obtained below z < 0.3 and when nine redshifts are obtained above z > 0.3. We discuss the improvements in this catalogue's identification of cluster using 33 340 redshifts, with Δ z phot /Δ z spec ∼ 100, over other photometric and spectroscopic surveys, as well as presenting an update to previous (σ– L X ) and (σ–λ) relations. Finally, we present our cosmological constraints derived using the velocity dispersion function.